Severe Degloving Injury with Covid-19 Infection – Successful Outcome and Hard Lessons Learnt - Nair, Vipin V.; Sharma, Pawan; Katiyar, Anand; Sharma, Abhishek (Lietuvos chirurgija, 2021)
Here we share an interesting case of severe trauma with tissue loss to nearly half of the back and a lacerated perineum in a Covid-19 positive patient in septic shock. This article highlights our experiences and hard lessons learnt in successful management of this complicated injury. Managing severe trauma is a challenge especially with respiratory failure resulting from Covid-19 infection. The patient reported to the hospital during a very difficult period, when proper medical care was difficult as hospitals and wards were filled with Covid positive patients. Managing patients was difficult especially wearing personal protective equipment round the clock. It’s a challenge when an entire team of surgeon, anesthesiologist, nursing staff and paramedics, rose above their daily call of duty to save the patient for her children. It was a fight against time and an many unknown enemy over three months for the entire team. The challenge to save a middle-aged patient from the claws of death against all odds was really miraculous. It was highly rewarding to see the patient going back to the family with a smile.